2021
DOI: 10.3389/fvets.2021.652000
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Assessment of Antiviral Effect of Natural Compounds on Porcine Epidemic Diarrhea Coronavirus

Abstract: Organic acid and essential oils (EOs), well-known antimicrobials, could also possess antiviral activity, a characteristic which has not been completely addressed up to now. In this study, the effect of two organic acids (formic acid and sodium salt of coconut fatty acid distillates) and two single EO compounds (thymol and cinnamaldehye) was evaluated against porcine epidemic diarrhea virus (PEDV). The concentration used for each compound was established by cytotoxicity assays in Vero cells. The antiviral activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested that the antiviral activity against Coronavidae members can be attributed to metabolites such as phytol and polysaccharides [ 69 ], which we did not find in our study. Other researchers have reported a prominent role of organic acids in the viricidal effect, with one of the most prominent metabolites being formic acid, which can inhibit the replication of the porcine epidemic diarrhea virus (PEDV) [ 70 ]. According to the PCA, isobutyric acid was the metabolite with the highest impact on viricidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that the antiviral activity against Coronavidae members can be attributed to metabolites such as phytol and polysaccharides [ 69 ], which we did not find in our study. Other researchers have reported a prominent role of organic acids in the viricidal effect, with one of the most prominent metabolites being formic acid, which can inhibit the replication of the porcine epidemic diarrhea virus (PEDV) [ 70 ]. According to the PCA, isobutyric acid was the metabolite with the highest impact on viricidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, formic acid has no function in any anti-PEDV activity in the early steps of the viral cycle with the only exception of a slight effect of viral inactivation at the lowest PEDV MOI. Formic acid at a dose of only 1,200 ppm can effectively inhibit PEDV replication in Vero cells ( 109 ). However, the combination of essential oil and benzoic acid enhances the degradation of PEDV RNA ( 110 ).…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%